(untitled) (Revista Cientifica Ingenio Magno, 2023)
The comparative analysis of thermally treated steel microstructures is a research topic that aims to examine the resulting microstructural characteristics from different heat treatments applied to steels. Through a comprehensive review of related research works, the effects of variables such as temperature, exposure time, and cooling rates on phase formation and distribution of microstructural constituents are analyzed. This analysis allows for an understanding of the relationship between the microstructure and the mechanical properties of steels, such as hardness, tensile strength, and toughness. Various heat treatments were conducted, including water and oil quenching, normalizing, and annealing, on a total of 15 specimens of AISI 1045, AISI 4140, and AISI 8620 steels. The objective was to examine the resulting microstructures and phases in each steel type after each treatment. Metallographic analyses were performed on both commercially acquired and treated steels, resulting in micrographs and hardness measurements to confirm the transformations. Furthermore, the phases present in the studied materials were identified, aiming to analyze the specific impact of each heat treatment on the three steel types. Clear microstructural changes occurring in metallic materials when subjected to heat treatments, in this case applied to three steel types, were observed